The wear resistance research of the rail contact surface depending on the grinding process - Pavlo Protsenko; Yurii Borodii; Mykola Bobyr; Eckart Uhlmann; Janis Thalau; Pavlo Lypovka (Mechanics and Advanced Technologies)
Background. Continuous mechanical loads on the rails during its contact with the wheel lead to an accumulation of residual stresses in the surface layers of the rails, resulting in fast-growing fatigue cracks. In addition, the interaction of the wheel and the rail leads to micro-and macro-slip during their contact, abrasive wear, as well as plastic deformation of the rail. Rail grinding is the repair method by which defective material layers removes from the rail surface, provides the necessary accuracy of size and shape as well as surface quality.